Exploring how arm movement moderates the effect of lower limb muscle fatigue on dynamic balance in healthy youth - Borgmann, Katharina; Ferdenhert, Jendrik; Neyses, Alexandra C.; Bauer, Julian; Hill, Mathew W.; Muehlbauer, Thomas (Frontiers in Sports and Active Living, 2024)
Background: In young adults, there is evidence that free arm movements do not help to compensate muscle fatigue-induced deteriorations in dynamic balance performance. However, the postural control system in youth is immature, and as a result, the use of arm movements may provide a compensatory 'upper body strategy' to correct fatigue-related balance impairments. Thus, the purpose of the present study was to compare the effects of free versus restricted arm movement on dynamic balance performance prior and following exerciseinduced muscle fatigue.Methods: Forty-three healthy youth (19 females; mean age: 12.8 ± 1.9 years) performed the Y Balance Test-Lower Quarter before and immediately after a fatiguing exercise (i.e., repetitive vertical bipedal box jumps until failure) using two different arm positions: free (move the arms freely) and restricted (keep the arms akimbo) arm movement.Muscle fatigue (p ≤ 0.033; 0.10 ≤ ηp 2 ≤ 0.33) and restriction of arm movement (p ≤ 0.005; 0.17 ≤ ηp 2 ≤ 0.46) resulted in significantly deteriorated dynamic balance performance.However, the interactions between the two did not reach the level of significance (p ≥ 0.091; 0.01 ≤ ηp 2 ≤ 0.07).Our findings indicate that the use of an 'upper body strategy' (i.e., free arm position) has no compensatory effect on muscle fatigue-induced dynamic balance deteriorations in healthy youth.